Предмет: Алгебра,
автор: Nameno2000
4(2x-1)^2-3(x+4)^2-19-13x^2 упростить выражение
Ответы
Автор ответа:
0
4(2х-1)²-3(х+4)²-19-13х²=0
4(4х²+1-5х)-3(х²+16+8х)-19-13х=0
16х²+4-20х-3х²-48-24х-19-13х=0
13х²-57х-63=0
Д=b²-4ac;D=
4(4х²+1-5х)-3(х²+16+8х)-19-13х=0
16х²+4-20х-3х²-48-24х-19-13х=0
13х²-57х-63=0
Д=b²-4ac;D=
Похожие вопросы
Предмет: Химия,
автор: rainbowunicornUwO
Предмет: Математика,
автор: samirbeks
Предмет: Литература,
автор: nastya20oct06
Предмет: Алгебра,
автор: DjVampirka
Предмет: Математика,
автор: Аноним